Penerapan Psikoedukasi Keluarga terhadap Kemampuan Keluarga dalam Merawat Pasien Skizofrenia - Meyunda Alfriyani (Journal of Telenursing (JOTING), 2026)
This study aims to determine the effect of family psychoeducation on improving families' ability to care for schizophrenia patients. The research method used was a literature review through electronic databases and websites, namely Pubmed, Proquest, ScienceDirect, and Google Scholar. The results showed that of the nine research articles, one article stated that family psychoeducation was effective in improving the ability to care for schizophrenia patients and reducing the signs and symptoms of schizophrenia patients' problems. Several articles also stated that family psychoeducation was able to prevent relapse in schizophrenia patients. Conclusion: Family psychoeducation is effective and can provide benefits in improving family knowledge and abilities in caring for schizophrenia patients. Keywords: Caregiving Skills, Family Psychoeducation, Schizophrenia